2001
DOI: 10.1580/1080-6032(2001)012[0093:ce]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Centipede envenomation

Abstract: Five episodes of envenomation by centipedes in 2 patients are reported. These arthropods are fast-moving, frightening in appearance to some, and may display aggressive behavior. However, stings from these centipedes, like most found worldwide, caused no serious morbidity or mortality. Common effects included intense local pain, erythema, induration, and necrosis, as well as mild constitutional symptoms. All resolved without sequelae. Treatment included pain control, wound care, and tetanus immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 6 publications
1
52
0
12
Order By: Relevance
“…Four studies reported envenomation, however Stern et al (2000), and Roll and Schmid-Grendelmeier (2005) reported that the entomologists in their studies were allergic to the venom, hence these have been classified as allergies. Bush et al (2001) and Isbister et al (2004) did not specify the type of reaction, and have therefore been classified as unspecified venom reactions. The majority of the included studies (n¼ 42) addressed allergies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported envenomation, however Stern et al (2000), and Roll and Schmid-Grendelmeier (2005) reported that the entomologists in their studies were allergic to the venom, hence these have been classified as allergies. Bush et al (2001) and Isbister et al (2004) did not specify the type of reaction, and have therefore been classified as unspecified venom reactions. The majority of the included studies (n¼ 42) addressed allergies.…”
Section: Resultsmentioning
confidence: 99%
“…For scorpions and Scolopendromorpha envenomation there was no testing regarding allergies, hence it is unclear whether these reactions were allergic and/or toxic. Reported reactions to Scolopendromorpha were pain, burning sensation, swelling, red streak, felt 'unwell', bleeding, erythema, throbbing, 'sprained' sensation, nausea, pruritus, lump, flushed feeling, and altered sensation (Bush et al, 2001), and Scorpiones reactions including pain, tingling, burning, bleeding, hypersensitivity and paraesthesia (Isbister et al, 2004). The symptoms for other allergic reactions are summarised in Table 6 where there was clinical evidence of the allergy (see Appendix A).…”
Section: The Types Of Adverse Work-related Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…When detected, secondary and systemic effects of centipede envenomation should be treated with standard therapy (Bouchard et al 2004;Bush et al 2001;McFee et al 2002;Steen et al 2007;Veraldi et al 2010). Standard proper wound care and tetanus vaccination update (if needed) is also indicated.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…Centipedes are chiefly nocturnal, live in humid environments, are venomous invertebrates and have exoskeleton and jointed legs. Centipede bites are benign common accidents and usually present with local pain, edema, and local hyperthermia [1]. The treatment includes analgesics and local anesthesia to decrease pain.…”
mentioning
confidence: 99%